2021
DOI: 10.1002/ajoc.202100314
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Bio‐based Redox Electrolyte using Pivalic Acid and Ascorbic Acid for the Activated Carbon‐based Supercapacitor Fabrication

Abstract: Supercapacitor is considered a promising energy storage device due to its high‐power density and high specific capacitance. Electrode materials and electrolytes are major components of supercapacitors. The most used electrolytes are not biocompatible, which limits their practical applications. Bio‐electrolytes often cause low performances of supercapacitors. However, the inadequate performances of bio‐electrolytes for supercapacitor applications could be improved using redox molecules. Here, we are reporting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 60 publications
0
38
0
Order By: Relevance
“…Maxwell, NEC, Tokin, Panasonic and the Russian Econd company contributed most to the world market. Helmholtz developed the concept of double-layer capacitance by identifying its properties in 1879, but it took decades for double-layer capacitance to be exploited for energy storage [31,34]. In 1957, Becker reported that smaller capacitors could be used as energy storage devices.…”
Section: History Of Supercapacitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maxwell, NEC, Tokin, Panasonic and the Russian Econd company contributed most to the world market. Helmholtz developed the concept of double-layer capacitance by identifying its properties in 1879, but it took decades for double-layer capacitance to be exploited for energy storage [31,34]. In 1957, Becker reported that smaller capacitors could be used as energy storage devices.…”
Section: History Of Supercapacitorsmentioning
confidence: 99%
“…The second component is the electrolyte [34,55,58], a conduction source which can be found in every device [96][97][98]. In a typical capacitor, a dielectric is present.…”
Section: Components Of Supercapacitormentioning
confidence: 99%
“…It is observed that the CV shapes deviate from the perfect rectangular shape beyond the potential of 1.0 V because of the dissociation of water and O 2 /H 2 gas evaluation, shown in Figure 5 a. 34 Furthermore, the ESPW was confirmed from the GCD results of a fixed current density of 1.0 A g –1 as the shape of the GCD curve appeared symmetrical triangle with extended discharge time within the potential of 1.0 V, shown in Figure 5 b. The electrochemical rate capability of as prepared ternary hybrid was done by conducting CVs with different scan rates from 10 to 100 mV s –1 , and GCD performance was conducted at 1.0, 2.0, and 4.0 A g –1 within potential range 0 to 1 V, shown respectively in Figure 5 c,d.…”
Section: Resultsmentioning
confidence: 95%
“…Another key element of an SC is the electrolyte comprising salt and solvent, which typically contributes to determining the operating potential window (OPW) of SCs. The capacitance value depends on the size difference, ionic conductivity, mobility of the system, and thermal and electrochemical stability based on its reactivity at different temperature conditions [110] . Depending on the types of electrolytes (aqueous, organic/inorganic, and ionic liquids) used in SCs, it can offer different OPWs to the SC, either a wide or narrow OPW, affecting the total energy density and power density of the system [115] .…”
Section: Working Principle Of Supercapacitorsmentioning
confidence: 99%